Differential Ability of Agonists to Express Distinct Pools of Fibrinogen (Gpllb/llla) Receptors which Can Mediate the Aggregation of Human Platelets - Watts, Ian S; Keery, Rebecca J; Lumley, Philip (Thrombosis and Haemostasis, 1989)
We have investigated the effect of two procedures that modify human platelet surface membrane glycoprotein (Gp) IIb and IIIa complexes upon whole blood platelet aggregation to a range of agonists. (A) Irreversible disruption of complexes by temporary (30 min) Ca2+-deprivation with EGTA at 37° C. (B) Binding of a monoclonal antibody M148 to the complex. EGTA exposure abolished aggregation to ADP, adrenaline and PAF. In contrast, full aggregation curves to collagen and U-46619 could still be established. EGTA exposure reduced M148 binding to platelets by 80%. Excess M148 abolished aggregation to ADP, PAF, collagen and U-46619. However, upon removal of unbound antibody from platelets full aggregation curves to collagen and U-46619 but not to ADP and PAF could be re-established. Thus human platelet aggregation to ADP, PAF and adrenaline appears absolutely dependent upon surface membrane GpIIb/IIIa complexes. In contrast, collagen and U-46619 cause expression of an additional distinct pool of Gp complexes inaccessible to EGTA and M148 in unstimulated platelets which is intimately involved in aggregation to these agonists.
Keywords: Extracellular calcium; Glycoprotein IIb/IIIa complex; Platelet fibrinogen receptors; Platelet aggregation